Investigating nasal deviation and need for corrective grafts in Iranian patients referring for aesthetic rhinoplasty - Motamed, Sadrolah; Niazi, Feizollah; Hassanpour, Seyed Esmail; Mahmoudvand, Hormoz; Amali Amiri, Hadi; Azargashb, Eznolah; Nadri, Sedigheh; Rouintan, Abdolreza (Researcher Bulletin of Medical Sciences, 2018)
Introduction: Rhinoplasty is one of the most challenging plastic surgeries in which achieving the desired outcome requires high techniques as well as a great aesthetic vision. The aim of the current study is to compare the functional and aesthetical priority of the unilateral placement of the spreader graft in the concave side of the nose over the convex side. Material and Methods: A descriptive study was conducted on 282 volunteer patients for primary rhinoplasty during from 2011 to 2013. Nasal examination and desirable lab data’s photography of face and nose was taken. Preoperative nasal deviation from midline of face was evaluated with the guide of preoperative photo. Then it was compared with intraoperative finding and nasal septal deviation evaluated with type and number of cartilage graft . Results: A total of 282 of patient consisting of 195 females and 87 males with a age range of 17-51 years old underwent primary rhinoplasty and were evaluated. Most operations performed on patients who are under 30 years old and 69.1% of patients were females. Two hundred and eighty cases were done through open rhinoplasty and 2 case closed rhinoplasty. One hundred and ninety one patients (67.7%) for the cause of aesthetic and 91 patients (32.3%) for the cause of aesthetic plus functional came for primary rhinoplasty. Amount of pre-operative nasal deviation degree was (71.5%) and intra operative septal deviation was (91.5%), which septorhinoplasty was mostly performed (91.5%). Fifty nine patients (20.9%) had mild deviation and 146 (51.5%) had moderate and 77 (27.3%) patients had sever deviation. Conclusion: Success in rhinoplasty needs to pay attention to the patients desire as well as careful nasal analysis and evaluation of its subunits together. More than 99% of patients had an open septorhinoplasty that mostly had moderate nasal deviation (51.8%). These patients were treated with spreader graft (unilateral or bilateral) ± scoring or batten graft usage of different surgical techniques was like other scientific and reliable centers in world.